TREND ANALYSIS OF REGIONAL ORIGINAL INCOME IN SIMEULUE REGENCY - Rosyah, Lidiana; Marzuki, Marzuki; Nurlela, Nurlela; Munandar, Munandar (PT. Radja Intercontinental Publishing, 2022)
AbstractThis study aims to analyze the trend of local tax revenues, regional levies, separated regional wealth management results, other legitimate local revenue and zakat in the Simeulue Regency Government during the 2011-2021 period. This study uses secondary data from 2011-2021. obtained from the Realization Report of the Regional Revenue and Expenditure Budget. The data analysis method used is descriptive quantitative and trend analysis. Trend analysis in this study, is used to see the tendency ofregional taxes, regional levies, results of separated regional wealth management, other legitimate PAD and zakatin each data series during the period 2011 - 2021. The results of the study found that the trend of local taxes increased, the trend of regional levies decreased, the trend of separated regional wealth increased, other trends in legitimate pads increased and the trend of zakat increased . This shows that the increase in the realization of regional taxes, regional levies, separated regional wealth, other legal pads, and zakat increases along with the increasing trend.